The Influence of Farmers' Income and Social Status on Children's Education - Emayanti, Murni; Fauza, Hendri; Perkasa, Ripho Delzy (research, training and philanthropy institution Natural Aceh, 2025)
This study used a quantitative descriptive approach and involved 161 farmers. Data were collected through questionnaires and documentation and tested for normality, homogeneity, linearity, multicollinearity, and hypothesis. The analysis results show that for the social status variable, the tcount value of 1.672 exceeds the ttable value of 1.655, which indicates that the alternative hypothesis (Ha) is accepted, which results in the approval of the null hypothesis (Ho). Multicollinearity and hypothesis. The analysis results show that for the social status variable, the tcount value of 1.672 exceeds the ttable value of 1.655, which indicates that the alternative hypothesis (Ha) is accepted, which results in the approval of the null hypothesis (Ho). Therefore, the null hypothesis is better than the alternative hypothesis. This suggests that Income does not significantly affect outcomes. The F test shows an equal influence of social status and Income on the observed variables with a significance value of 0.183. However, the calculated Fvalue (1.716) is lower than the Ftable (3.05), which indicates that the combined effect is not statistically significant. This finding indicates that, while Income has no significant impact on the variables under study, social status has a significant impact. This finding serves as a basis for improving policies that help farmers, especially regarding Income.